Penerapan Pembelajaran Tematik untuk Meningkatkan Pembelajaran Matematika, Seni, dan Bahasa Inggris di SDN Locare 01 Bondowoso - Sintya Fadillah; Nadifa Nuril Diana; Daniah Humam Bafadal; Qurratul Faisah Firdaus; Octavia Dwike Ramadhani; Fadlurahman Nafis Januar; Shine Asmaul Khusnah Mandiaru; Weldy Nugroho Detagory; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This study aims to analyze and identify effective strategies for improving the quality of learning in Mathematics, Art, and English subjects at SDN Locare 01 Bondowoso. The background of this research highlights several challenges in achieving optimal learning outcomes, particularly in enhancing students’ interest and connecting the learning materials with real-life contexts. The research employed a descriptive qualitative method, with data collected through classroom observations, in-depth interviews with teachers and the school principal, as well as document analysis of curriculum materials and students’ learning outcomes. The learning improvement strategies explored include the implementation of Contextual Teaching and Learning (CTL) in Mathematics, project-based learning for Art and English subjects, and the integration of simple technology and interactive learning media to create more engaging learning experiences. The findings indicate that integrated learning strategies focusing on active student participation significantly improve conceptual understanding, creativity, and learning motivation. These results align with Wahyuni (2016), who found that contextual learning helps students connect mathematical concepts with daily life situations. Similarly, Marni (2022) emphasized that project-based learning in Art effectively fosters students’ creativity and collaboration, while Ajiza and Rahman (2021) demonstrated that Audio-Lingual and Total Physical Response (TPR) methods increase elementary students’ motivation in learning English. This study recommends enhancing teacher collaboration, providing continuous professional development, and conducting regular evaluations to sustain innovative learning practices and ensure the continuous improvement of education quality at SDN Locare 01 Bondowoso.